Beyond Joint Forest Management - Sharma, R. C. (Indian Forester, 2000)
The role and importance of forests in maintaining the life support system in terms of ecological, economic and socio-cultural framework is better understood now and accordingly the incongruous forestry administration is undergoing a paradigm shift from regulatory to participatory management. Whilst sporadic efforts were made by some self-initiated groups and individuals, the National Forest Policy, 1988 and the enabling resolution of the Government of India, 1990 coupled with recent Constitutional Amendment conferring ownership rights of minor forest produce on village level organizations, form a watershed in the saga of Joint Forest Management (JFM) in India. Foresters, though well equipped with silvicultural armoury, had to tread hitherto unknown path of sociological variables. In order to inculcate attitudinal change and capacity building, national as well as regional level training institutes are organizing orientation and training programmes covering wide array of social issues including theory and tools of participatory techniques. However, with an impressive 36,075 village level committees, jointly managing around 10.24 million hectares forests in 22 states, the outcome has been uneven for variety of reasons. JFM being driven by the "helplessness" of the state and with little mindset change, foresters tend to hold on to their territorial and silvicultural moorings and perceive JFM as a tool to win the locals by offering employment and some usufruct sharing. People, on the other hand with their past experience have little faith in state apparatus. Their aspiration is, not to remain mere passive wage earners but to become active partners and owners of the assets created. The ground reality is that apart from policy regulations and their enforcement, complex social values born out of history, culture and traditions, determine the out come. The message is loud and clear- wherever a resilient and adaptive management has taken good care of these human sensitivities, chances to succeed are better.